Incidental tuberculoid granuloma in bone marrow biopsy in 17-year-old male patient: A case report (Indian Journal of Case Reports, 2019)
Granulomas are susceptible to infrequent finding in bone marrow biopsies and may be associated with a broad spectrum of infectious and non-infectious disorders. The incidence of bone marrow granulomas is reported in 0.3% to 3% of bone marrow biopsies with tuberculoid granulomas constituting 6% to 48% of cases. Here, we report the case of a 17-year-old boy with a history of fever (pyrexia of unknown origin). There was no organomegaly and lymphadenopathy with incidental tuberculoid granuloma on bone marrow biopsy.